2020
DOI: 10.22424/jdsb.2020.38.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Yogurt Fermented by Bacteriocin-producing Pediococcus acidilactici

Abstract: Physical and sensory characteristics of commercial yogurts are important aspects for consumer acceptability. In addition, beneficial functions of commercial yogurts are also emphasized for the probiotic dairy products. The aim of this study was to investigate the functional properties of yogurts with the combination of bacteriocin-producing Pediococcus acidilactici. Yogurts fermented with commercial starter culture (control yogurt) and control yogurt together with P. acidilactici HW01 (yogurt+HW01), P. acidila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A previous study reported that bacteriocin, a representative AMP used in food, is hydrolyzed when reacted with the human proteolytic enzyme and loses its antimicrobial activity. Therefore, the antimicrobial activity of bacteriocin does not remain and is used as a food preservative [11,46]. iTME showed a result of losing antibacterial activity by human-derived trypsin and chymotrypsinin this study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A previous study reported that bacteriocin, a representative AMP used in food, is hydrolyzed when reacted with the human proteolytic enzyme and loses its antimicrobial activity. Therefore, the antimicrobial activity of bacteriocin does not remain and is used as a food preservative [11,46]. iTME showed a result of losing antibacterial activity by human-derived trypsin and chymotrypsinin this study.…”
Section: Discussionmentioning
confidence: 77%
“…As for the stability as food preservatives, sorbic acid has been reported to have a very stable antimicrobial activity at pH 2-7, after heating at 85 • C for 2 h, or at a high salt condition [45]. Nisin, a natural preservative derived from bacteria and sold as a commercial product, has also been shown to have antimicrobial activity at pH 2-6 and even when heated to 121 • C [46]. In addition, GSE also retains its antibacterial activity at pH 4-10 and 150 • C [44].…”
Section: Discussionmentioning
confidence: 99%